Motivation to Learn English When Facing Difficulties and Fatigue Among ESL Students of University of Arkansas - Erizar, Erizar (VELES Voices of English Language Education Society, 2019)
This study aims to explore motivation to learn English when facing difficulties and fatigue among ESL students of University of Arkansas  based on the level of their study ,gender, age, living status (living alone and living with others). To collect the data, graduate and undergraduate degree holders were asked to take the survey voluntarily. The result of research  indicates that there is no significant different between undergraduate holder (mean = 3.54; std.dev = 0.48) and graduate degree holders  (mean = 3.64; std.dev = 0.52 , based on independent t-test, t= -1.270, p-value >0.05) However, when comparing the motivation based on the gender, the data signify the difference between male(mean = 3.65; std.dev = 0.51) and female .undergraduate degree holders(mean= 3.46; std.dev = 0.45),  in which male undergraduate degree holders are more motivated than females.  Also,  there is a significant different motivation between adult learners based on their living situation. The data shown that adult learners who live with others (mean= 3.63;std.dev= 0.47) have higher motivation than those who live alone (mean = 3.42; std.dev= 0.56) based on independent t-test ( t= -2.222, p-value <0.05). In addition, when motivation to learn is compared across age groups of participants, it indicates no significant difference (F = 1.282, p-value > 0.05).